(untitled) (Journal of Geography and Environmental Management, 2018)
Numerous projects of the world organizations UN, UNWTO, UNESCO, UNDP and the programs of the states located on the Great Silk Road contribute to the economic growth and integration of the countries of the Eurasian countries, as well as the revival of tourism on a world-wide route. In this regard, the most relevant is the development of nomadic tourism on the Great Silk Road as an active form of the human movement. Kazakhstan has great opportunities for organizing this type of tourism. Unique monuments of history, archeology, architecture, ancient cites included in the UNESCO World Heritage List will contribute to the activation of nomadic tourism and, in general, the strengthening of regional cooperation in the field of tourism. The article considers theoretical foundations of nomadic tourism, the possibilities of its organization on the Kazakh area of the Great Silk Road. The classification of nomad tourism is presented, the advantages of its development are analyzed, the SWOT-analysis of the development of nomadic tourism on the Great Silk Road is compiled, , conducted a sociological survey. At the same time, the authors suggest a tourist route along the international transport corridor “Western Europe - Western China”. In the future, it is planned to make a combined route, using mixed vehicles.